Frequency and site mapping of HIV-1/SIVcpz, HIV- 2/SIVsmm and other SIV gene sequence cleavage by various bacteria restriction enzymes: Precursors for a novel HIV inhibitory product - Wayengera, Misaki; Wilson, Byarugaba; Henry, Kajjumbula (African Journal of Biotechnology, 2007)
Resistance, toxicity and virologic failure have underlined the need to develop new HIV inhibitory products. Base on the natural bacteria “restriction modification system” antiviral immune model, we set out to analyze the effects of various restriction enzymes on the HIV genome. A computer simulated model using Web cutter Version 2.0, and cytogenetic analysis. 339 restriction enzymes from Promega database, 10 HIV-1/SIVcpz genes, 10 HIV-2/SIVsmm genes and 10 other SIV genes. Gene sequences were fed into Web cutter 2.0 set to search enzymes with at least 6 recognition base pairs (palindromes). A background in vitro cytogenetic control analysis using HIV-1/SIVcpz GAG, POL and ENV genes was done. Of the 339 enzymes used, 238 (70.2%) cleaved the HIV-1/SIVcpz A1.BY.97.97BL006_AF193275 genome with 9037 bp compared to 225 (66.4%) and 219 (64.6%) for the HIV-2/SIVsmm genome (9713 bp) and other SIV B.FR.83.HXB2_LAI_IIIB_BRU_K03455 genome (9719 bp), respectively. Individual genes had differing but potent susceptibility to the enzymes, with a 98.9% Web cutter PPV (95%CI, 97.2%- 99.6%) for in vitro cytogenetics. The natural bacteria RMS antiviral immune model offers precursors for developing novel HIV and other viral therapeutic molecules.
Keywords: HIV/AIDS; Novel Microbicides Strategies; Restriction Modification Systems; HIV genomes; Combination-Microbicides